The Role of Corporate Governance in the Determinant of Carbon Emission Disclosure in Indonesia - Adhissa Aztiannisa Aulia; Zulfikar (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study aims to identify the role of corporate governance in carbon emissions disclosure in Indonesia, especially in the context of business size, industry type, and profitability. Against the backdrop of increasing awareness of climate change issues and the Indonesian government's commitment to reducing emissions, carbon emissions disclosure is becoming increasingly relevant. Through a quantitative approach, this study analyzes secondary data sourced from companies listed on the Indonesia Stock Exchange (IDX) during the period 2019 - 2022. The sample selection method applied is purposive sampling with a total of 155 from 2019-2022. This study explores whether business size, industry type, and profitability affect carbon emissions disclosure, and how the board of directors functions as a moderating variable in the relationship. The results are expected to contribute to corporate governance practices and regulations related to carbon emissions disclosure in Indonesia, as well as assist companies in improving the integrity and transparency of their environmental reporting.